Development and Validation of High-Performance Thin Layer Chromatographic Method for Estimation of Acyclovir - Raksha, Pai; Vanita, Somasekhar; Vijayanthimala, Purushottaman; Athira, Chandran (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The antiviral medication genre comprises the synthetic purine nucleoside analogue acyclovir, which particularly is used to treat varicella-zoster and herpes simplex virus infections. By incorporating into viral DNA to stop further synthesis, acyclovir limits DNA synthesis and viral multiplication. The investigation of an economical alternative was spurred by the existence of the currently used HPLC and UV techniques for acyclovir analysis, which are recognized for their solvent-intensive character. The innovation offers a more cost-effective method of pharmaceutical analysis along with improving sustainability. Materials and Methods Using a CAMAG Linomat 5 sampler, the samples were spotted in the form of bands on a precoated silica gel plate using a CAMAG microliter syringe. The application rate was kept constant at 100 nL/sec and the spacing between the tracks was set. Chloroform, ethanol, isopropyl alcohol and strong ammonia (2:4:3:1 v/v/v/v) constitute the mobile phase. The development process was linear ascending in a twin trough glass chamber that was saturated with a mobile phase. To estimate acyclovir, densitometric scanning was carried out in the absorbance mode at 254 nm. Results With r2=0.9974, the calibration plots’ linear regression analysis results demonstrated a strong linear association. The limit of quantification was 11.7726 μg/mL, whereas the limit of detection was 3.884 μg/mL. Conclusion According to statistical analysis of the data, the approach was found to be precise, accurate, repeatable, sensitive and selective for the analysis of acyclovir. The technique will work well for routine quality control when estimating acyclovir as a bulk medication.
Keywords: HPTLC; ICH guidelines; Method development; Acyclovir